Analisis Customer Satisfying dan Knowledge Sharing Dalam Optimalisasi Formulasi Promotion Pemasaran Produk Lokal di Yogyakarta dan Palangka Raya - Kristinae, Vivy (Universitas Pendidikan Ganesha, 2021)
Research in the field of marketing management to optimize the formulation of promotions from customer satisfaction and knowledge sharing in realizing the economic welfare of local product business actors. The research was conducted in two cities in Indonesia that have a culture with batik products as an aesthetic regional icon in meeting customer needs. Batik has an appeal and philosophy which is a cultural heritage, economically it has value-added products to advance the region from increasing income. SDL research theory in providing a strategy to improve service quality in terms of promotion based on customer needs. The research was conducted on 300 batik entrepreneurs in Yogyakarta and in Palangka Raya. This type of quantitative research with statistical tools SPSS 24.0 shows significant positive results of customer satisfaction and knowledge sharing increasing the optimization of marketing promotions by 71%. The implications of the research as a marketing strategy in increasing the income of local product business actors, from optimizing marketing promotions for the economic welfare of business actors.